DAMPAK UTANG LUAR NEGERI TERHADAP PEREKONOMIAN INDONESIA - Indra Darmawan (Universitas Sanata Dharma, 2022)
This study aims to describe: 1) how is the development of Indonesia’s foreign debt; 2) what are the impacts of foreign debt on the Indonesian economy; and 3) what are the policy alternatives that can be taken to minimize the negative impact of foreign debt on the Indonesian economy. This type of research is descriptive qualitative research. Data collection techniques used are observation and literature/documentation studies. Literature study is a data collection technique by conducting a review study of books, literature, notes, and reports that have to do with the problem being solved. The data in this study were obtained from various publications of government institutions such as Bank Indonesia, the Central Statistics Agency, and the Ministry of Finance of the Republic of Indonesia. The results of the study show that: 1) External debt is able to encourage Indonesia’s economic growth in economic sectors that absorb high external debt. 2) Domestic saving shows an increasing role. 3) The swap scheme can be considered as a solution to the high external debt. Keywords: foreign debt, impact, debt to serve ratio, public saving, Indonesian economy